Clinical and anatomopathological findings of lipid-related lesions in wild and pet birds from the State of Paraíba, Northeastern Brazil - Hodias S. Oliveira-Filho; José L.C. Duarte; Gabriel F. Paranhos; Rafael L. Oliveira; Roberto C. Farias; Jeann Leal de Araújo (Pesquisa Veterinária Brasileira, 2023)
ABSTRACT: Diseases related to lipid metabolism disorders are reported in several orders of birds, especially in psittacines, and include obesity, atherosclerosis, hepatic lipidosis, egg yolk coelomitis, lipomas, liposarcomas, xanthomas and xanthogranulomas. This study describes epidemiological, clinical and anatomopathological aspects of 28 cases involving lipid-related lesions in wild and pet birds from Northeastern Brazil. The cases were selected from 313 avian patients referred to the UFPB Veterinary Hospital from 2018 to 2022. Lipid-related tumors were the most frequent lesions, followed by obesity, hepatic steatosis, egg yolk coelomitis, atherosclerosis and lipemia. The Psittaciformes order was the most affected, and an erroneous diet (excess consumption of sunflower seeds, bread, crackers, rice, etc.) was identified as the main risk factor for the development of these lesions, which reinforces the need to warn bird owners and caretakers about the importance of adequate nutrition. Forty-nine percent of the reported tumors were in the pericloacal region, which makes lipomas and xanthomas an important differential diagnosis for nodules in this location of birds, especially psittacids.